PAINKILLERS, THEIR CHEMICAL COMPOSITION, AND THE MECHANISM OF THEIR EFFECT ON THE HUMAN BODY (World Bulletin of Public Health, 2025)
This article discusses the chemical composition, classification, and biochemical mechanisms of pain relief of analgesic drugs in the human body. An analysis is provided using examples of paracetamol, novocaine, and aspirin. Additionally, based on the latest scientific research from 2024– 2025, information about new analgesics, current issues in the field and their corresponding solutions, as well as global statistics on the usage of analgesics, are presented.